Trends in Sickle Cell Disease Mortality: 1979-2020. - Karkoska, Kristine A.; McGann, Patrick T. (Pediatrics, 2024)
BACKGROUND AND OBJECTIVES: Although sickle cell disease (SCD)-related childhood mortality in the United States significantly improved in the 1990s, unclear is the trend in SCD-related mortality more recently given the continued disparities faced by this minoritized population. In this analysis, we aimed to (1) compare the overall and age-specific mortality rates from 1999 to 2009 vs 2010 to 2020 with a particular focus on the age of transition and (2) determine the most common causes of death for the US SCD population for 2010 to 2020. METHODS: We analyzed publicly available data from the Centers for Disease Control and Prevention WONDER database, a compilation of national-level mortality statistics from 1979 to 2020 derived from death certificates compiled by the National Center for Health Statistics. We searched by all individuals of all ethnicities, sexes, and ages using the underlying cause of death. RESULTS: The crude mortality rate for individuals with SCD for 2010 to 2020 was 1.6 per 1000 000 individuals, which was significantly lower than the period 1999 to 2009 (crude rate 1.7 per 1000 000, P < .0001). In addition, the mean age at mortality of those with SCD was older in 2010 to 2020 (43 years) versus 1999 to 2009 (39 years). However, there remains a significant increase in mortality rate in the 20 to 24 year age group versus 15 to 19 years (1.7 per 1000 000 versus 0.7 per 1000 000, P < .0001), corresponding with the age of transition from pediatric to adult centers. In addition, 39% of underlying causes of death were not caused by SCD, but rather primarily chronic conditions, including cardiovascular, cerebrovascular, malignancy, and renal disease. The study has several limitations mostly because of the imperfections of administrative data sources, including inaccuracies in diagnoses codes, risking over or undercounting. CONCLUSIONS: Although the US SCD-related mortality rate continues to decrease, the age of transition to adult care is a particularly vulnerable time in the lives of this marginalized group. Innovative and expanded approaches to care are greatly needed.